Microreactor-assisted synthesis of α-alumina nanoparticles. Issue 9 (15th June 2020) - Yu, Haibin; Wang, Mengdi; Zhou, Jinghui; Yuan, Biao; Luo, Jin; Wu, Wei; Chen, Zan; Yu, Ruixiang
Abstract: In this paper, nanosized α-Al2 O3 powders were synthesized with the aid of a high throughput impinging stream microreactor. It was demonstrated that the as-prepared powders exhibited better dispersity and more homogeneous distribution of particle size than that prepared by conventional parallel flow precipitation method due to the drastic collisions and homogeneous explosive nucleation in microchannel during the precipitation process. The effects of calcinating temperature and time on the morphology, phase composition and particle size of α-Al2 O3 were systematically studied. Comparatively well dispersed and crystallized α-Al2 O3 powders with higher sintering activity were obtained by calcinating the as-prepared precursors at 1200 °C for 2 h in air. The specific surface area of α-Al2 O3 powders was above 20 m 2  g −1 and average particle size was about 110 nm with higher sintering behavior. From room temperature to 1520 °C, the green compact exhibited shrinkage of 19.34%. This work opens a door for developing ultrafine α-Al2 O3 powders with uniform size distribution, high crystallinity, and excellent thermal expansion property.